Material adhesion and stresses on friction stir welding tool pins. (June 2014) - Mehta, M.; De, A.; DebRoy, T.
<x content-type="archive" xml:space="preserve">Abstract</x> During friction stir welding, polygonal tool pins experience severe stresses and, under certain conditions, loss of functionality due to adhesion of plasticised material on their surfaces. The extent of adhesion is analysed for various pin geometry and welding conditions based on the theory of machining. The effective stresses on the polygonal pins are evaluated following the principles of mechanics. The results show that the polygonal pins with fewer sides can avoid permanent adhesion of plasticised material at higher weld pitch, which is defined as a ratio of welding speed and tool rotational speed. The computed pin geometries for minimum adhesion are compared with the pin profiles recommended by various investigators based on independent experiments. The computed stresses show that pins with larger number of sides will experience lower stresses for any given set of welding variables.